Risk Factor For Early Breastfeeding Cessation - Lestari, Pratiwi Puji; Aulia, Fika (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
Introduction: early cessation of breastfeeding is still a common issue in many parts of the world). Several factors contributed to the cessation of breastfeeding due to the state of the mother's mental health during breastfeeding. This will have an impact on less optimal nutrition that the baby receives for his growth and development. Method: literature review using 2 databased PubMed and Google Scholar. Results: The risk factors for early weaning in breastfeeding mothers are barriers to breastfeeding, pumping and expressing breast milk, support and education, stress and mental health, cultural and social factors, perception of not getting enough breast milk. Conclusion: Identification and analysis of risk factors for early breastfeeding cessation is essential to address this problem effectively. The results of the identification of risk factors for early weaning in breastfeeding mothers are barriers to breastfeeding, pumping and expressing breast milk, support and education, stress and mental health, cultural and social factors, perception of not getting enough breast milk.